Foundations of design - Davis, Jeff (Jeff G.) (Boston, Massachusetts Wadsworth, Cengage Learning, 2013)
Covers the major topics in the fundamentals of design. This book features a selection of contemporary and graphic design examples that aid students in making connections from the principles of design through to a final work. It offers students real world examples, as well as the online peer review and instructor critique tool, Art Studio.
1. Design -- 2. Format -- 3. Line -- 4. Shape -- 5. Size -- 6. Color -- 7. Texture -- 8. Composition -- 9. Space -- 10. Grouping -- 11. Contrast -- 12. Balance -- 13. Emphasis -- 14. Movement -- 15. Unity.
Keywords: Design; Color in design